The Status and Meaning of Criminal Procedure: An exploration of the reception of DNA evidence in the criminal process - Aarli, Ragna (Bergen Journal of Criminal Law & Criminal Justice, 2013)
Volume 1, Issue 1, 2013, pp. 63–74.